1997
DOI: 10.1246/cl.1997.297
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Ligand Displacement of Ru(cod)(cot) with Trimethylphosphine to Give fac-Ru(6-η1:1-3-η3-C8H10)(PMe3)3

Abstract: Selective ligand displacement of the cod ligand in Ru(cod)(cot) (1) [cod: 1,5-cyclooctadiene, cot: 1,3,5-cyclooctatriene] with trimethylphosphine gives fac-Ru(6-η1:1-3-η3-C8H10)(PMe3)3 (3) in benzene at 50 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…As it is well established, the adduct [Ru(η 4 -cod)(η 4 -cot)(η 1 -depe)] was initially formed. 4e, 19 Then, simultaneous release of cot (detected by 1 H NMR) and a decrease in the resonances for the adduct (in the 31 P{ 1 H} NMR) give rise to a new intermediate [Ru(C 2 H 3 OCOEt)(cod)(depe)] III (Scheme 6). Interestingly, the intermediate complex III was the major species detected in solution when we limited the amount of depe (1 equivalent/Ru), whereas in the presence of an excess amount of depe (>2 eq/ Ru), III gradually converted into the oxidative addition product [Ru(η 1 -C 2 H 3 )(OCOEt)(depe) 2 ] 8b (Scheme 6).…”
Section: Mechanistic Considerations For the C-o Bond Cleavage Of Viny...mentioning
confidence: 99%
See 1 more Smart Citation
“…As it is well established, the adduct [Ru(η 4 -cod)(η 4 -cot)(η 1 -depe)] was initially formed. 4e, 19 Then, simultaneous release of cot (detected by 1 H NMR) and a decrease in the resonances for the adduct (in the 31 P{ 1 H} NMR) give rise to a new intermediate [Ru(C 2 H 3 OCOEt)(cod)(depe)] III (Scheme 6). Interestingly, the intermediate complex III was the major species detected in solution when we limited the amount of depe (1 equivalent/Ru), whereas in the presence of an excess amount of depe (>2 eq/ Ru), III gradually converted into the oxidative addition product [Ru(η 1 -C 2 H 3 )(OCOEt)(depe) 2 ] 8b (Scheme 6).…”
Section: Mechanistic Considerations For the C-o Bond Cleavage Of Viny...mentioning
confidence: 99%
“…IR (KBr, cm Ϫ1 ): 1604, 1355. 13 C{ 1 H}NMR (75.5 MHz, C 6 D 6 ): δ 9.3 (d, J = 33 Hz, Me of depe), 18.0 (m, CH 2 of depe), 19.4 (m, CH 2 of depe), 20.9 (q, J = 11 Hz, CH 2 of depe), 120.0 (q, J = 5 Hz, -CH᎐ ᎐ CH 2 ), 128.3-127.7 (p-OCOPh overlapped with resonances for C 6 D 5 H), 129.1 (s, m-OCOPh), 129.7 (s, o-OCOPh), 140.0 (s, ipso-OCOPh), 165.1 (q, J = 10 Hz, -CH᎐ ᎐ CH 2 ), 170.9 (s, OCOPh).…”
Section: Preparation Ofmentioning
confidence: 99%
“…Treatment of 1 with basic and compact monodentate phosphines such as PMe 3 or PMe 2 Ph resulted in the immediate formation of the known mono phosphine adduct Ru(η 4 -1,5-COD)(η 4 -1,3,5-COT)L [L = PMe 3 (2a), PMe 2 Ph (2b)], but further warming of 2a or 2b at 50 ЊC for 24-33 h led to the unexpected substitution reaction of the 1,5-COD ligand with these phosphines to form di-valent complexes Ru(6-η 1 :1-3-η 3 -COT)L 3 [L = PMe 3 (3a), PMe 2 Ph (3b)] in 25-42% isolated yields, respectively (Scheme 2). 19,20 These complexes 3a-b were fully characterised with their Xray structure analyses. The molecular structure of 3b is depicted in Fig.…”
Section: Reactions Of Ru( 4 -15-cod)( 6 -135-cot) (1) With Lewis Base...mentioning
confidence: 99%
“…of DMPE and DEPE initially formed Ru(η 4 -1,5-COD)(η 4 -1,3,5-COT)(bidentate phosphine-κ 1 P) (2f,g), which then yielded Ru(η 4 -1,5-COD)(DMPE-κ 2 P,PЈ)(DMPE-κ 1 P) (9f ) or Ru(η 4 -1,5-COD)-(DEPE-κ 2 P,PЈ)(DEPE-κ 1 P) (9g) at 50 ЊC for 2.5 h in 18 and 49% yields respectively, by the selective release of 1,3,5-COT (Scheme 4). 19 They are basically similar complexes to those reported by Chaudret, 12 but further heating of 9 at 50 ЊC for 18 h gave an analytically pure dinuclear complex [Ru(η 4 -1,5-COD)(DMPEκ 2 P,PЈ)] 2 (µ-DMPE-κ 2 P,PЈ) (10f ) and [Ru(η 4 -1,5-COD)(DEPEκ 2 P,PЈ)] 2 (µ-DEPE-κ 2 P,PЈ) (10g) in 14 and 41% yields, respec-Scheme 3 tively. However, addition of DEPE to 10g at room temperature for 1.5 h reproduced 9g in 72% yield.…”
Section: Reaction Of Ru( 4 -15-cod)( 6 -135-cot) (1) With Bi-and Tri-...mentioning
confidence: 99%
“…Because such a bunch of these phosphine complexes 2a-c was formed from 1/PMe3 without addition of phenyl vinyl ether under the similar conditions (2a: 66%, 2b: 8%, 2c: 20%)[18,22], phenyl vinyl ether did not engage with the formation of 2a-c at all. However, we accidentally found that addition of water intothe mixture involving 2a-c and phenyl vinyl ether caused complete conversion of 2c into white precipitates of [(Me3P)3Ru(-OH)3Ru(PMe3)3] + [OPh] -•HOPh (3•HOPh) in 36% yield based on 1 (81% yield based on 2c), while 2a remained intact.…”
mentioning
confidence: 99%